Seismic Source of the Chile 2010 Earthquake from Inversion of Geodetic Data and Observations - Jiménez, César (2018)
On February 27, 2010 an earthquake of magnitude 8.8 Mw (according to USGS) shook the center-southern region of Chile with a balance of more than 500 deaths. As a coseismic effect, a tsunami was generated which destroyed many coastal villages, as well as the permanent crustal deformation. This coseismic deformation can be quantified by geodetic measurements: GPS, field observations at the littoral and InSAR satellite interferometry data. From the analysis and processing of the geodetic data it is possible to obtain the parameters that characterize the distribution of the seismic source through an inversion process, in which the simulated data is compared with the observed data using the non-negative least squares method. The results show the existence of two main asperities located to the north and south of the epicenter. The maximum slip or dislocation was 17.3 m located in the northern side of the rupture area. The calculated "geodetic"scalar moment is 1.25 × 1022 Nm, which is equivalent to a magnitude of 8.7 Mw.